Sangkan Paran: Estetika Jawa dalam Cerita Rahwana, Novel Anak Bajang Mengiring Angin Karya Sindhunata - Supriyanto, RM. Teguh (Kamaya: Jurnal Ilmu Agama, 2025)
The story of Rahwana is found in the novel Anak Bajang Menggiring Angin, although an episode but it is the core of Javanese cultural aesthetics based on the sources of Islamic Mataram in Krato Surakarta Hadiningrat and Ngayogyakarta Hadiningrat. Rahwana was born from the lust of anger that overflowed because of the desire that exceeded human standards from Sukesi, his mother. Sangkan Paran is a concept from the answer to the knowledge of Jendra Hayuningrat Pangruwating Diyu literature. Humans come from divine light (nur) and reside in the deepest heart (nur), ideals (mind) or reason and feeling. Reason is still wrapped in four passions, anger, aluwamah, sifiyah, and mutmainah. The four elements of passion must be present and balanced so that life is peaceful, harmonious and in harmony.